Isolation and identification of potential probiotic lactic acid bacteria (Lactobacillus casei and Bifidobacterium) from raw and fermented camel milk during storage - Malini, N S; Raghav , Pramod K. (Journal of Postharvest Technology, 2021)
The aim of this study is to isolate and molecularly characterize LAB present in raw and fermented milk. The sample was collected in local  areas in Jaipur Rajasthan. The identification of the selected LAB strains and their genetic relatedness was performed based on 16S rDNA  gene sequence comparisons. They differed in their different probiotic characteristics such as tolerance to acidic pH, resistance to bile  tolerance, and antibacterial activity. In conclusion, the isolates Lactobacillus casei, Enterococcus durans, Lactobacillus Plantarum, and  Bifidobacterium were most probably high quality with probiotic potentials. We speculate studying the synergistic effects of bacterial  combinations might result in a more effective probiotic potential, Lactobacilli species (42.90%). Enterococcus spp isolates represented  28.26%, The remaining isolates were Lactobacillus casei and Bifidobacterium that represented 4.87% and 2.42%. We suspect in raw and  fermented camel milk was rich in LAB and has capable probiotic potential.
Keywords: Lactobacilli; LAB; Bile tolerance; 16S rDNA; Bifidobacterium; probiotics